Fresh Bitter Melon Fruit (Momordica charantia) Attenuated Oxidative Stress, Fibrosis and Renal Injury in Carbon Tetrachloride Treated Rats - Sagor, Md Abu Taher; Reza, Hasan Mahmud; Tabassum, Nabila; Rahman, Md Moshfequr; Alam, Md Ashraful (Dhaka University Journal of Pharmaceutical Sciences, 2018)
Chemical or drug-induced kidney damage is increasing every year and the end-stage renal disease is becoming a burden for health care system of many countries. Oxidative stress may be a crucial pathway for the development of end-stage renal disease. Thus, natural antioxidant or plant-based therapy would be a better alternative to protect renal function against chemical-induced renal damage. To determine these aspects we evaluated renoprotective effects of M. charantia in carbon tetrachloride administered rats. A 10% w/w mixture of fresh fruits of M. charantia was given with the chow food every day to CCl4 treated rats. After fourteen days, all animals were sacrificed and the kidneys were examined to observe the possible protective effects of M. charantia against CCl4 induced toxicity. The CCl4 treated rats showed increased oxidative stress parameters and decreased antioxidant enzymes activities. Supplementation of 10% w/w M. charantia fruits in CCl4 administered rats prevented the oxidative stress and restored the antioxidant enzymes activities. M. charantia fruits supplementation also prevented the rise of uric acid and creatinine concentration in plasma of CCl4 treated rats. Furthermore, histological studies showed that supplementation of 10% w/w M. charantia fruits prevented the collagen deposition, immune cell migration and iron deposition in kidney sections of CCl4 treated rats. The results of this study revealed that the fruits of M. charantia may protect oxidative stress-mediated damage in kidneys due to CCl4 administration, which is mediated probably via the restoration of anti-oxidant enzyme functions. Dhaka Univ. J. Pharm. Sci. 16(2): 205-214, 2017 (December)